Analisis Degradasi Lingkungan Pada Penduduk Perkotaan Di Negara Anggota ASEAN - Dava Rahmatullah; Indanazulfa Qurrota A‘yun (Journal of Management Specialists, 2024)
This study aims to analyze environmental degradation in urban populations in ASEAN Member States in 2007-2020. This study uses secondary data obtained from the World Bank website and World in Data. The data analysis method uses panel data regression with the Fixed Effect Model (FEM) approach and the Eviews 10 analysis tool. The results of data processing show that there are urban population variables that have a positive and significant effect on carbon dioxide emissions, then renewable energy consumption variables and electricity use have a negative and significant effect on carbon dioxide emissions. While the economic growth variable has no effect on carbon dioxide emissions.